Avian Diversity of the Masako Forest Reserve after Anthropization (Tshopo Province, Democratic Republic of the Congo) - Elie Pelove Bugentho; Glodi Lotana Lotana; Bienvenu Ligili Kapita; Jean Saidi Bilama; Jean Paul Koto-Te-Nyiwa Ngbolua; Sylvestre Mbalitini Gambalemoke; Dieudonné Agenong’a Upoki (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Anthropization is one of the main drivers of forest ecosystem degradation and strongly affects biodiversity. This study analyzes the comparative diversity of the avifauna in the Masako Forest Reserve (RFM) before and after anthropogenic disturbances. Data were collected between February and July 2024 using mist nets and observation points across different habitat types, including young and old fallows, croplands, and forest fragments. The results show a marked decline in avifauna, with a local loss of approximately 77% of the species initially recorded. Specialized forest species are the most affected, while the persistent species are mostly generalists, tolerant to disturbed environments. Recolonization remains very low. The disappearance of species with concerning conservation status, such as Psittacus erithacus, highlights a real risk of local extinction and underscores the negative impact of human activities on the ecological integrity of the RFM, calling for strengthened conservation measures.